2017
DOI: 10.3892/ol.2017.6742
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgetin induces cell death in breast cancer cells via downregulation of the estrogen receptor

Abstract: Abstract. Ginkgetin is a natural biflavonoid isolated from the leaves of Ginkgo biloba, and is characterized by its anti-inflammatory and anti-viral activities. Although numerous studies state that it has also antitumor activity, the anti-proliferative effect of ginkgetin and the underlying mechanism in breast cancer cells have not yet been investigated. In the present study, ginkgetin inhibited the cell viability of MCF-7 and T-47D cells dose-dependently, and suppressed the expression of the estrogen receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…41 Ginkgetin is a natural biflavonoid with anti-inflammatory, antiviral, and antitumor properties. 42 Icariin, a flavonoid glycoside, is the main bioactive ingredient of Epimedii herba and is a promising therapeutic agent for the treatment of various disorders because of its antiapoptotic, anti-inflammatory, and antioxidant activities. 43 , 44 …”
Section: Active Chemical Compounds Of Epimedii Herbamentioning
confidence: 99%
“…41 Ginkgetin is a natural biflavonoid with anti-inflammatory, antiviral, and antitumor properties. 42 Icariin, a flavonoid glycoside, is the main bioactive ingredient of Epimedii herba and is a promising therapeutic agent for the treatment of various disorders because of its antiapoptotic, anti-inflammatory, and antioxidant activities. 43 , 44 …”
Section: Active Chemical Compounds Of Epimedii Herbamentioning
confidence: 99%
“…Ginkgetin (GGT) was identified as one of the most potent inhibitors of TRPV4 in the screening. Since previously published reports showed that GGT has an anti-inflammatory and anti-adipogenic effect, we selected GGT for further functional analysis on TRPV4-dependent macrophage proatherogenic activity 48 , 49 , 52 , 53 .
Figure 1 Semi high-throughput screening-based identification of ginkgetin as a novel TRPV4 inhibitor from a library of natural compounds.
…”
Section: Resultsmentioning
confidence: 99%
“…Four compounds of them were isolated for the first time from Z. floridana leaves. These compounds were tested previously in other studies against breast and colon cell lines in vitro and they showed cytotoxic effects [ 2 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], which could account for the cytotoxic effect of the n -butanol fraction of Z. floridana. The potent toxoplasmocidal effect of n -BuOH fraction encouraged us to investigate and predict the possible mechanisms of these compounds to inhibit T. gondii using in silico molecular docking study.…”
Section: Discussionmentioning
confidence: 99%